2016
DOI: 10.3892/mmr.2016.4879
|View full text |Cite
|
Sign up to set email alerts
|

Increased expression of dermatopontin and its implications for testicular dysfunction in mice

Abstract: An array of specific and non-specific molecules, which are expressed in the testis, have been demonstrated to be responsible for testicular function. Our previous study revealed that dermatopontin (DPT) is expressed in Sertoli cells of the testis, however, its roles in testicular function remains somewhat elusive. In the present study, CdCl2- and busulfan-induced testicular dysfunction models were used to investigate the implications of DPT expression for testicular function. The mRNA and protein expression le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 38 publications
1
4
0
Order By: Relevance
“…Moreover, transcriptomic and RT-qPCR analyses highlighted an upregulation of Dpt expression in 2-week-old prKO and in 2-month-old srKO and prKO testes (Supplemental Figure 7G), indicating increased dermatopontin production by both altered adult STs and the hyperplastic stromal compartment. Our results are consistent with previous data demonstrating that the dermatopontin excessive production in SCs induced BTB alterations, vacuole formation, and GC loss (25). However, srKO and prKO comparative analyses also revealed precocious and higher growing Dpt transcript levels associated with tumor expansion in prKO testes.…”
Section: Resultssupporting
confidence: 93%
“…Moreover, transcriptomic and RT-qPCR analyses highlighted an upregulation of Dpt expression in 2-week-old prKO and in 2-month-old srKO and prKO testes (Supplemental Figure 7G), indicating increased dermatopontin production by both altered adult STs and the hyperplastic stromal compartment. Our results are consistent with previous data demonstrating that the dermatopontin excessive production in SCs induced BTB alterations, vacuole formation, and GC loss (25). However, srKO and prKO comparative analyses also revealed precocious and higher growing Dpt transcript levels associated with tumor expansion in prKO testes.…”
Section: Resultssupporting
confidence: 93%
“…The tracker diffused inside ST and confirmed a drastic loss of BTB sealing in both srKO and prKO (6 weeks of age) demonstrating that SC failed to provide an appropriate structural dynamic for the GC maturation across the seminiferous epithelium. Moreover, transcriptomic and RTqPCR analyses (srKO/prKO testes) highlighted an earlier and huge up-regulation of Dpt expression in 2-week-old prKO testes which could amplify the BTB alterations, the vacuole formation and the germ cell loss as it was demonstrated in transgenic mice overexpressing Dpt in SC (25) ( Figure 4O).…”
Section: Pka Overactivation Alters Sertoli Cell Polaritymentioning
confidence: 79%
“…Another extracellular protein known to play a role in inhibition of proliferation is DPT, which is involved in the organization of collagen fibrils in the extracellular matrix [ 53 , 54 ]. Additionally, it was demonstrated that an increased abundance of DPT is associated with testicular dysfunction [ 54 , 55 , 56 ]. OGN was shown to inhibit proliferation in cardiac smooth muscle tissue and influences apoptosis and cell migration [ 57 , 58 ].…”
Section: Discussionmentioning
confidence: 99%